Mesenchymal Stem Cell Derived Extracellular Vesicles Ameliorate Kidney Injury in Aristolochic Acid Nephropathy - Kholia, Sharad; Herrera Sanchez, Maria Beatriz; Cedrino, Massimo; Papadimitriou, Elli; Tapparo, Marta; Deregibus, Maria Chiara; Bruno, Stefania; Antico, Federica; Brizzi, Maria Felice; Quesenberry, Peter J.; Camussi, Giovanni (Frontiers in Cell and Developmental Biology, 2020)
Limitations in the current therapeutic strategies for the prevention of progression of chronic kidney disease (CKD) to end stage renal disease has been a drawback to improving patient recovery. It is therefore imperative that a solution be found to alleviate this problem and improve patients health and well-being overall. Aristolochic acid (AA) induced nephropathy, a type of nephrotoxic CKD is characterised by cortical tubular injury, inflammation, leading to interstitial fibrosis. Extracellular vesicles derived from human bone marrow mesenchymal stem cells (MSC-EVs) display therapeutic properties in various disease models including kidney injury. In the current study, we intended to investigate the ability of MSC-EVs on ameliorating tubular injury and interstitial fibrosis in a mouse model of aristolochic acid nephropathy (AAN). The chronic model of AAN comprised of administering NSG mice with a repeated injection of AA intraperitoneally, followed by a three day incubation period and then inoculating with MSC-EVs intravenously. This routine was performed on a weekly basis for 4 consecutive weeks together with the monitoring of body weight of all mice. Blood and tissue samples were collected post sacrifice. All animals administered with AA developed kidney injury and renal fibrosis. A gradual loss of body weight was observed together with deterioration in kidney function. Although no significant recovery was observed in weight loss following treatment with MSC-EVs, a significant reduction in: blood creatinine, tubular necrosis, and interstitial fibrosis were observed. In addition, infiltration of CD45 positive immune cells and fibroblasts, which were elevated post AA induced injury, were also reduced significantly by MSC-EVs. Kidneys were also subjected to molecular analyses to evaluate the regulation of pro-fibrotic genes. MSC-EVs significantly downregulated AA induced upregulation of the pro-fibrotic genes α-Sma, Tgfb1 and Col1a1. Furthermore, meta-analyses of miRNAs downregulated by MSC-EVs such as miR21 revealed the regulation of multiple pathways involved in kidney injury including fibrosis, inflammation, and apoptosis. These results therefore suggest that MSC-EVs could play a regenerative and anti-fibrotic role in AAN through the transfer of biologically active cargo that regulates the disease both at a protein and genetic level.